The Myth of Manliness in Irish National Culture, 1880-1922 - Valente, Joseph (Book collections on Project MUSE., 2011)
The construct of manliness remains very much alive today, underpinning the neo-imperialist marriage of ruthless aggression to the sanctities of duty, honor, and sacrifice. Mapping its earlier colonial and postcolonial formations clarifies its continuing danger and appeal."--Jacket.